Alih Media Arsip Vital di Dinas Kearsipan dan Perpustakaan Kota Kediri - Rachel Izza Tsani; Erlangga Andi Sukma (Indo Publishing, 2026)
This article discusses the implementation of vital records media transfer project at the Department of Archives and Library of Kediri City. Vital records are records whose existence is a basic requirement for the operational continuity of record creators, cannot be renewed, and cannot be replaced if damaged or lost. The media transfer process is carried out through several stages, namely preparation, scanning and editing, electronic and cloud-based filing, and preparation of media transfer record lists. The records transferred include Building Construction Permits and Student Master Books of State Elementary Schools in Kediri City. The results of the project show that media transfer improves the accessibility, security, and efficiency of vital records management, supports legal accountability, and accelerates public information services. The main constraints faced are limited equipment and the absence of authentication policies. This project contributes to the development of archival science, particularly in the field of reprography and records digitization.